Lectures on Solid Mechanics - Enzo Marino; Claudio Borri; Michele Betti (Firenze University Press, 2008)
This volume presents the theoretical basics of solid mechanics collecting the lectures held by the Authors for the course of Mechanics of Solids to environmental engineering students at the University of Florence. Lectures on Solid Mechanics is organized in two parts. The first one introduces the theory of three-dimensional elasticity where, after a preparatory synthesis of the basic concepts of mathematics and geometry, the fundamental framework of strain and stress in elastic bodies are introduced. Then the classical law of linear elasticity is presented and finally the part concludes with the "Principle of Virtual Work and variational methods". Moreover, at the end of selected chapters the essential notions of the theory of shells are discussed. The second part concerns the traditional theory of beams focusing on the four fundamental cases: beam under axial forces, terminal couples, torsion, bending and shear. The Readers addressed by this volume are mainly the undergraduate students of Engineering Schools.
Keywords: ingegneria ambientale; Ingegneria; Fisica